2017
DOI: 10.1158/2159-8290.cd-16-1080
|View full text |Cite|
|
Sign up to set email alerts
|

Phase I Dose-Escalation Study of Taselisib, an Oral PI3K Inhibitor, in Patients with Advanced Solid Tumors

Abstract: Taselisib is a potent and selective tumor growth inhibitor through PI3K pathway suppression. Thirty-four patients with locally advanced or metastatic solid tumors were treated (phase I study, modified 3+3 dose escalation; 5 cohorts; 3-16 mg taselisib once daily capsule). Taselisib pharmacokinetics were dose-proportional; mean half-life was 40 hours. Frequent dose-dependent, treatment-related adverse events included diarrhea, hyperglycemia, decreased appetite, nausea, rash, stomatitis, and vomiting. At 12 and 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
117
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 36 publications
14
117
1
Order By: Relevance
“…We used trametinib, which is a potent and selective MEK1/2 inhibitor that was approved by the Food and Drug Administration for the treatment of BRAF V600E‐mutant NSCLC in combination with the BRAF inhibitor dabrafenib . For PI3K inhibition, we selected taselisib, which has been shown in early‐phase clinical trials to be of clinical benefit for solid tumors harboring PIK3CA alterations . The details about these cell lines, the reagents, and the antibodies for western blot analysis are included in the Data .…”
Section: Methodsmentioning
confidence: 99%
“…We used trametinib, which is a potent and selective MEK1/2 inhibitor that was approved by the Food and Drug Administration for the treatment of BRAF V600E‐mutant NSCLC in combination with the BRAF inhibitor dabrafenib . For PI3K inhibition, we selected taselisib, which has been shown in early‐phase clinical trials to be of clinical benefit for solid tumors harboring PIK3CA alterations . The details about these cell lines, the reagents, and the antibodies for western blot analysis are included in the Data .…”
Section: Methodsmentioning
confidence: 99%
“…Taselisib (GDC-0032; Table S1) inhibits p110α, p110γ and p110δ but not p110β, and furthermore has some selectivity for PIK3CA mutant proteins. A phase I dose-escalation trial of taselisib reported a 36% response rate for patients with PIK3CA mutant tumors, versus 0% in patients whose tumors lacked a PIK3CA hotspot mutation (Juric et al, 2017). In a phase 2 trial of fulvestrant plus taselisib, patients with ER+, mutant PIK3CA -expressing breast cancer had substantially better overall responses than patients with wild-type PIK3CA tumors (Dickler et al, 2016).…”
Section: Therapeutic Targeting Of the Pi3k Pathway In Cancermentioning
confidence: 99%
“…PI3Kα inhibitors have shown improved clinical outcome in estrogen receptor (ER)-positive and PIK3CA mutant breast cancers that have elevated PI3K signaling (Juric et al, 2017, 2018), but not all tumors are sensitive to these inhibitors. We have observed a highly uniform adaptive tumor response to PI3K inhibitors that is characterized by an increase in ER-dependent transcription, which mediates therapeutic resistance (Bosch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%